Phytochemical Screening of Termite's Mushroom in Nepal - Aryal, Hari Prasad; Budhathoki, Usha (Journal of Natural History Museum, 2015)
This paper reports the qualitative phytochemical analysis of Termitomyces microcarpus (Berk & Broome) R. Heim of family Tricholomataceae collected from the termite nest of the forests in west, center and east of tropical, subtropical and temperate regions of Nepal. The sample was harvested fresh, sundried, pulverized and analyzed according to standard procedures. Screening revealed the presence of volatile oil, alkaloid, carotenoid, steroid, triterpenoids, fatty acid, emodins, flavonoid, coumarin, anthracene glycoside, anthocyanadine glycoside, tannins, saponins, glycosides, polyurenoid and polyoses in the ethereal, methanolic and aqueous extracts. There were significant differences in the phytochemical composition of the samples collected from east, center and west eco-zones and tropical, subtropical and temperate climatic regions. There was definite co-relation between the traditional application of Termite’s mushrooms and possession of secondary metabolites, which supports the scientific basis for the traditional medicinal system. Results showed that the consumption of wild edible mushroom that act as a good dietary supplement and it may be valuable in drug development. J. Nat. Hist. Mus. Vol. 27, 2013: 107-119